Activation of protein kinase C in the spinal cord produces mechanical hyperalgesia by activating glutamate receptors, but does not mediate chronic muscle-induced hyperalgesia - Audette KM; Sluka KA (SAGE Publishing, 2006)
Abstract Background Protein kinase C (PKC) in the spinal cord appears to mediate chronic injury-induced pain, but not acute nociceptive pain. Muscle insult results in increased release of glutamate spinally, and hyperalgesia that is reversed by spinal blockade of NMDA and non-NMDA glutamate receptors. Therefore, we hypothesized that spinal activation of PKC 1) mediates the late phase of hyperalgesia 1 week after muscle insult, and 2) produces mechanical hyperalgesia through activation of NMDA and non-NMDA glutamate receptors. Results Rats were implanted with intrathecal catheters for delivery of drugs directly to the spinal cord. Mechanical withdrawal thresholds of the paw were determined using von Frey filaments. Intrathecal phorbol 12,13 dibutyrate (PDBu) produced a dose-dependent decrease in the mechanical withdrawal threshold of the paw that was prevented by pretreatment with the PKC inhibitor, GF109203X. Pretreatment with an NMDA receptor antagonist (AP5) or a AMPA/kainate receptor antagonist (NBQX) prevented the decrease in mechanical withdrawal threshold by PDBu. Two injections of acidic saline in the gastrocnemius muscle decreased the mechanical withdrawal thresholds of the paw bilaterally 24 h and 1 week after the second injection. However, blockade PKC in the spinal cord had no effect on the decreased withdrawal thresholds of the paw when compared to vehicle controls. Conclusion Spinal activation of PKC produces mechanical hyperalgesia of the paw that depends on activation of NMDA and non-NMDA receptors. Chronic muscle-induced mechanical hyperalgesia, on the other hand, does not utilize spinal PKC.